Stroke onset time affected outcomes in the young acute ischemic stroke patients treated with endovascular thrombectomy - Yu, Mengying; Lin, Jie; Debora, Asta; Lin, Kai; Lin, Mengqi; Lin, Ru; Xu, Haoli; Zheng, Mo; Zhou, Ying; Yao, Fei; Zheng, Kuikui; Huang, Yingbao; et al. (Frontiers in Neurology, 2025)
ObjectiveThe purpose of this study was to investigate the association between stroke onset time and prognosis after endovascular thrombectomy (EVT) in Acute Ischemic Stroke (AIS) patients at different ages.MethodsThe AIS patients who underwent endovascular thrombectomy (EVT) between August 2018 to June 2022 were collected retrospectively. The patients were divided into two onset time groups [day-onset (6:00 h−18:00 h) vs. night-onset (18:00 h−6:00 h)], and further divided into 4 onset age groups (< 55 y, 55–64 y, 65–74 y and 75+ y). The primary outcome was discharge National Institutes of Health Stroke Scale (NIHSS) score and secondary outcomes were malignant brain edema, hemorrhagic transformation (HT), and early vascular recanalization (mTICI ≥ 2b). Mediation analyses were applied to explore how malignant brain edema, HT, and early vascular recanalization affect the relationship between onset time and outcome.ResultsA total of 470 AIS patients were enrolled, of whom 68 patients were younger than 55 years. After adjusting for confounders, younger (< 55 y) day-onset AIS patients had worse discharge outcomes (discharge NIHSS≥16, OR = 0.136, 95%CI = 0.027–0.678, P = 0.015) and were more prone to neurological deterioration (ΔNIHSS ≥ 4, OR = 0.081, 95%CI = 0.012–0.544, P = 0.010), malignant brain edema (OR = 0.145, 95%CI = 0.027–0.798, P = 0.026), and HT (OR = 0.231, 95%CI = 0.057–0.946, P = 0.042), while early vascular recanalization was less likely to occur (OR = 0.118, 95%CI = 0.017–0.813, P = 0.007). Mediation analysis showed that stroke onset time → malignant brain edema → discharge NIHSS score pathway was significant (c' = −2.029, BC 95%CI = −6.217; −0.087).ConclusionsThe outcomes of night-onset young AIS patients treated with EVT were better than day-onset, which may be related to the diurnal difference of malignant brain edema. However, these results were related to a small subgroup of patients and given the methodological statistical limitations (multiple testing correction), these results are only driving hypothesis. Further research with larger patient sizes are required to validate these results and explore the underlying mechanisms.